Intelligent tumor tissue classification for Hybrid Health Care Units - Butt, Muhammad Hassaan Farooq; Li, Jian Ping; Ji, Jiancheng (Charles); Riaz, Waqar; Anwar, Noreen; Butt, Faryal Farooq; Ahmad, Muhammad; Saboor, Abdus; Ali, Amjad; Uddin, Mohammed Yousuf (Frontiers in Medicine, 2024)
Introduction In the evolving healthcare landscape, we aim to integrate hyperspectral imaging into Hybrid Health Care Units to advance the diagnosis of medical diseases through the effective fusion of cutting-edge technology. The scarcity of medical hyperspectral data limits the use of hyperspectral imaging in disease classification. Methods Our study innovatively integrates hyperspectral imaging to characterize tumor tissues across diverse body locations, employing the Sharpened Cosine Similarity framework for tumor classification and subsequent healthcare recommendation. The efficiency of the proposed model is evaluated using Cohen's kappa, overall accuracy, and f1-score metrics. Results The proposed model demonstrates remarkable efficiency, with kappa of 91.76%, an overall accuracy of 95.60%, and an f1-score of 96%. These metrics indicate superior performance of our proposed model over existing state-of-the-art methods, even in limited training data. Conclusion This study marks a milestone in hybrid healthcare informatics, improving personalized care and advancing disease classification and recommendations.